(untitled) (Fiep Bulletin - online, 2013)
The balance maintenance is possible through the structures integration as the motor system, the proprioception, the vestibular system and the vision. Dynamic Posturography bases on the knowledge that the balance results of the integration of the visual, vestibular and proprioceptive informations, and it tests the individual in different situations. The aim of this study was evaluate the balance in patients with anterior cruciate ligament (ACL) lesion, submitted or not to the surgical reconstruction, through Foam-Laser Dynamic Posturography, Trying to find proprioception alterations. A sample of 45 individuals of the masculine gender was used, being those divided in 3 groups: GBEF (before surgery) n=15, GPOS (postoperative) n=15 and GCTL (it controls) n=15. For the data collection, Foam-Laser Dynamic Posturography was used. The individuals were submitted to the accomplishment of sensorial organization test (SOT) in 6 different conditions. It met results statistically significant, being pointed out proprioceptive deficit in some tests of the GBEF in relation to the GPOS and GBEF in relation to the GCTL. It is concluded that the Foam-Laser Dynamic Posturography can be used as method of balance clinical evaluation in individuals with ACL lesions, standing out the proprioceptive component, even so this can just be evaluated grossly, with relationship to the deviations of the reference values.